2022
DOI: 10.1111/febs.16680
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin 1 deficiency in prostatic tumours is correlated with immune cell recruitment and controls the up‐regulation of cytokine expression post‐transcriptionally

Abstract: Plakophilin (PKP1) 1 is a member of the arm‐repeat family of catenins and acts as a structural component of desmosomes, which are important stabilizers of cell–cell adhesion. Besides this, PKP1 also occurs in a non‐junctional, cytoplasmic form contributing to post‐transcriptional regulation of gene expression. Moreover, PKP1 is expressed in the prostate epithelium but its expression is frequently downregulated in prostate cancers with a more aggressive phenotype. This observation may imply a tumour‐suppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This nding is consistent with previous studies that reported increased IL-6 levels in the peripheral blood of prostate cancer patients [28][29][30]. IL-6 is known to play a critical role in prostate-mediated immune responses and can stimulate humoral and cellular immune responses by acting on B and T lymphocytes, promoting their growth and differentiation, and participating in in ammation induced by follicular Th cells [27,28,31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This nding is consistent with previous studies that reported increased IL-6 levels in the peripheral blood of prostate cancer patients [28][29][30]. IL-6 is known to play a critical role in prostate-mediated immune responses and can stimulate humoral and cellular immune responses by acting on B and T lymphocytes, promoting their growth and differentiation, and participating in in ammation induced by follicular Th cells [27,28,31].…”
Section: Discussionsupporting
confidence: 93%
“…Paul Katongole and others also found increased IL-6 levels in the serum of prostate cancer patients [26]. These cytokines are mainly secreted by T and B lymphocytes and are important components of the immune response, playing important roles in various biological functions, including immune response against bacterial infections [27]. These results indicate that in ammation often occurs during the evolution of prostate cancer and these indicators may be essential in diagnosing the disease.…”
Section: Discussionmentioning
confidence: 93%
“…In general terms, RYBP expression appears to be downregulated in those cancer types, and low RYBP expression is associated with poor prognosis [77,82,84,85]. On the other hand, PKP1 appears implicated in the development of prostate, lung, and breast cancers, among others [35,38,39,46,73,86]. Based on these data, we hypothesized that PKP1 and RYBP could interact directly with each other, at least in some of those cancer cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…We have recently shown that PADI4 binds to ARM-PKP1 [54] and RYBP [33]. Furthermore, both proteins are implicated in the progression of several cancer types [18,38,46,73,74], and they can act as oncogenes or tumor suppressors. In fact, several studies have shown that the expression of RYBP is dysregulated in various human tumor tissues, including prostate [75,76], lung [77], liver, breast, hepatocellular carcinoma, glioblastoma [78], Hodgkin lymphoma, and cervical cancer [17,19,[79][80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…PKP1 depletion in vivo recruits immune cells to create a tumor-specific milieu. This new cancer environment may be tumor suppressive, accelerating tumor growth and progression [ 161 ].…”
Section: Chemokines/cxcrs and Pcamentioning
confidence: 99%